2021
DOI: 10.1038/s41598-020-79608-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of blood-based fibrosis biomarkers in patients with metastatic colorectal cancer receiving chemotherapy and bevacizumab

Abstract: A desmoplastic colorectal cancer stroma, characterized by excess turnover of the cancer-associated fibroblast derived collagens type III and VI, can lead to reduced drug-uptake and poor treatment response. We investigated the association between biomarkers of collagen type III and VI and overall survival (OS) in patients with metastatic colorectal cancer (mCRC). Serum samples were collected from 252 patients with mCRC prior to treatment with bevacizumab and chemotherapy. Serum concentrations of biomarkers refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…Moreover, among the formation of collagen type III (PRO-C3), VI (PRO-C6), and degradation of collagen type VI (C6M and C6Mα3), PRO-C3 was the most effective in predicting the survival outcome of metastatic colorectal cancer (mCRC) patients regardless of other risk factors [47]. In another study, specific fragments of degraded type I, III, and IV collagen and type III collagen formation in serum showed that stage IV metastatic patients could be distinguished from all other stages [42].…”
Section: Collagenmentioning
confidence: 99%
“…Moreover, among the formation of collagen type III (PRO-C3), VI (PRO-C6), and degradation of collagen type VI (C6M and C6Mα3), PRO-C3 was the most effective in predicting the survival outcome of metastatic colorectal cancer (mCRC) patients regardless of other risk factors [47]. In another study, specific fragments of degraded type I, III, and IV collagen and type III collagen formation in serum showed that stage IV metastatic patients could be distinguished from all other stages [42].…”
Section: Collagenmentioning
confidence: 99%
“…During the past few years, biomarkers originating from the fibrotic TME have gained more attention [18]. We and others have shown that non-invasive biomarkers measuring ECM turnover products from fibroblast-derived collagens are increased in various cancer types and predictive of survival and treatment response [19][20][21][22][23][24][25]. As an example, PRO-C11-511, a biomarker measuring the pro-peptide of type XI collagen has shown to be increased in serum from patients with PDAC and is predictive of survival [24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, C4G, a biomarker measuring granzyme B degraded type IV collagen, assesses T-cell response and can identify patients with malignant melanoma responding to immune checkpoint inhibitors [19]. Fibrillar collagens are the most well-studied collagens, and the two fibrillar fibroblast-derived collagens, type IIIand VI collagen, have shown potential as biomarkers in cancer [19,20,22,23,25,26]. Type III and VI collagens are present in most tissue within the interstitial matrix of the ECM and are augmented in many cancer diseases [20,[27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The COL6 family plays a critical role in cell adhesion ( 17 , 18 ), apoptosis, autophagy ( 19 ), and dystrophy ( 20 ). Interestingly, some members are involved in the growth and development of tumors ( 21 , 22 ). In previous studies, COL6A6 has been shown to be a cancer suppressor gene that acts as an independent prognostic marker for pituitary adenomas.…”
Section: Discussionmentioning
confidence: 99%